2013
DOI: 10.1161/circulationaha.113.001875
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Urgent Warfarin Reversal With Frozen Plasma Versus Prothrombin Complex Concentrate in the Emergency Department

Abstract: Backround-Physicians reverse patients' warfarin anticoagulation with frozen plasma or prothrombin complex concentrate.Our objective was to determine adverse event frequency after urgent reversal with frozen plasma versus the prothrombin complex concentrate Octaplex. Methods and Results-This natural before-after retrospective cohort study in 2 tertiary care emergency departments compared anticoagulation reversal with frozen plasma (September 2006-August 2008 and with Octaplex (September 2008-August 2010, witho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
65
3
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(72 citation statements)
references
References 20 publications
3
65
3
1
Order By: Relevance
“…24 One hour after the start of infusion, 69% Similarly, in a retrospective cohort study of FP vs Octaplex for anticoagulation reversal in the emergency department, the investigators found that the PCC resulted in faster reversal of warfarin with fewer adverse events, including heart failure and death, when compared with FP. 25 Frozen plasma…”
Section: Contraindicationsmentioning
confidence: 99%
“…24 One hour after the start of infusion, 69% Similarly, in a retrospective cohort study of FP vs Octaplex for anticoagulation reversal in the emergency department, the investigators found that the PCC resulted in faster reversal of warfarin with fewer adverse events, including heart failure and death, when compared with FP. 25 Frozen plasma…”
Section: Contraindicationsmentioning
confidence: 99%
“…31 Heparin bridging is not necessary, apart from in patients with certain mechanical valves. In a recent metaanalysis, heparin bridging for invasive procedures and surgery in patients receiving vitamin K antagonists for AF, prosthetic heart valve or venous thromboembolism conferred a greater than five-fold increased risk for bleeding, whereas the risk of thromboembolic events was not significantly different between bridged and nonbridged patients.…”
Section: Peri-procedural Anticoagulationmentioning
confidence: 99%
“…8,9 Consequently, until now, most of the evidence supporting the use of PCC for VKA reversal came from observational studies. 2,[10][11][12][13] In this issue of Circulation, Sarode et al 14 report the results of a phase III, open-label, noninferiority, randomized, controlled trial that compared a 4-factor PCC with fresh frozen plasma for urgent reversal of VKA-associated coagulopathy in 216 patients with acute bleeding. Despite the modest sample size and the fact that the trial enrolled 69 centers in the United States and Eastern Europe, the study took >2 years to complete.…”
Section: Article See P 1234mentioning
confidence: 99%